Characteristics of voltage sags in radial and loop system with satatic and dynamic loads - Ahmad Farris Shari (School of Electrical System Engineering, University Malaysia Perlis, 2011)
For some decades, power quality did not cause any problem, because it had no effect on most of the loads connected to the electric distribution system. When an induction motor is subjected to voltage sag, the motor still operates but with a lower output until the sag ends. However, the increased use of sophisticated electronics, high efficiency variable speed drive, and power electronic controller, power quality has become an increasing concern to utilities and customers. It can be caused by fault in the electrical network or by the starting of a large induction motor. Although the electric utilities have made a substantial amount of investment to improve the reliability of the network, they cannot control the external factor that causes the fault, such as lightning or accumulation of salt at a transmission tower located near to sea. This project intends to investigate characteristics of voltage sags in radial and loop systems with static and dynamic loads were the simulation will be using PSCAD/EMTDC software. Characteristics that have upon static and dynamic will be investigate on voltage, current and power that produces when the voltage sag occur. At the end of the project it is expected that a few suggestions can be made on the suitability of the techniques.